2020
DOI: 10.3390/diagnostics10020088
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Morphology in Children with Growth Hormone Deficiency and Turner Syndrome

Abstract: The review aims to collect and demonstrate recent knowledge about craniofacial morphology in growth hormone (GH)-deficient children and children with Turner syndrome. The review describes also the effects of growth hormone treatment on craniofacial morphology of children with growth hormone deficiency and Turner syndrome. Regardless of the disorder it accompanies, short stature is associated with similar craniofacial features characteristic of all short-statured children. Characteristic craniofacial features i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
1
10
0
5
Order By: Relevance
“…Craniofacial morphology and dental maturity in children with reduced somatic growth of different etiology have been recently reviewed [ 80 , 81 ]. Based on the published craniofacial and dental characteristics of children with isolated GH deficiency, with idiopathic short stature, small for gestational age and/or with intrauterine growth retardation, and of short-statured children of genetic origin (Silver-Russell syndrome, Turner syndrome, familial dwarfism), the authors concluded that children with short stature of different origins develop similar craniofacial characteristics, including smaller lengths of the cranial base and the mandible, and proportionately smaller posterior than anterior facial height, retrognathic face, and posterior rotation of the mandible.…”
Section: Gh/igf Axis Modulates the Morphology Of The Dento-alveolar Complex And Cranio-facial Bonesmentioning
confidence: 99%
“…Craniofacial morphology and dental maturity in children with reduced somatic growth of different etiology have been recently reviewed [ 80 , 81 ]. Based on the published craniofacial and dental characteristics of children with isolated GH deficiency, with idiopathic short stature, small for gestational age and/or with intrauterine growth retardation, and of short-statured children of genetic origin (Silver-Russell syndrome, Turner syndrome, familial dwarfism), the authors concluded that children with short stature of different origins develop similar craniofacial characteristics, including smaller lengths of the cranial base and the mandible, and proportionately smaller posterior than anterior facial height, retrognathic face, and posterior rotation of the mandible.…”
Section: Gh/igf Axis Modulates the Morphology Of The Dento-alveolar Complex And Cranio-facial Bonesmentioning
confidence: 99%
“…Since orthodontic treatment is a common need among diseases with craniofacial abnormalities (Barton and Crowder, 2010;Hwang and Cha, 2004;Wójcik and Beń-Skowronek, 2020), the benefits of muscle IGF-I in the mandibular region were further studied. In mIgf1 +/+ mice, the mandibular plane angle was smaller during the active growth in the equivalent adolescent phase when compared to WT animals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, local IGF-I administration into the muscle had the capacity to alter bone growth. This posits a major benefit in targeting specific bone growth either vertically or horizontally for correcting any disproportionate growth in the craniofacial bone that occurs in children with GHD, as children with GHD tend to have smaller mandible and facial proportions when compared to the calvarial region (Wójcik and Beń-Skowronek, 2020). Although the present study did not address if this effect could be extended to adult animals, the influence of IGF-I on an adult mandibular condylar growth plate may be akin to the present study given that secondary cartilage contains undifferentiated mesenchyme differing to the appendicular primary skeletal cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations